Nursing Informatics: A Historical Bibliometric Analysis - Blažun Vošner, Helena; Carter-Templeton, Heather; Završnik, Jernej; Kokol, Peter (Computers, informatics, nursing, 2020)
Computers were introduced into nursing care areas in the early 1950s; however, nursing informatics' historical roots emerged much earlier. Contrary to previous studies, which used manual review of the nursing informatics literature, we employed an automated, electronic approach with specialized software to identify its historical roots. The corpus of nursing informatics literature was harvested from Scopus using "informatic*" in information source titles, abstracts, and keywords, limited to the "subject area = nursing." The search resulted in 3805 publications containing 57 057 valid references. Fifteen historical sources were identified, the two oldest written by nursing pioneer Florence Nightingale. Other historical roots represent specific foundational and core scholarly works offering insight into the genesis and sustainment of particular bodies of literature in the field of informatics. Our study revealed that the field of nursing informatics has sought to respond to global health concerns and that through intensive development nursing informatics has become an independent research area affecting nursing advancements in general. Additionally, nursing informatics has influenced other disciplines. This study offered an in-depth look at nursing informatics literature, using a systematic approach to identify historical roots and analyze the evolution of topics and themes to gain more information about knowledge development in nursing informatics.